Toward On-Line Slag Composition Analysis: Optical Emissions from Laboratory Electric Arc - Pauna, H.; Tuomela, A.; Aula, M.; Turunen, P.; Pankratov, Vladimir; Huttula, M.; Fabritius, T. (Springer, 2021)
Electric arc furnaces and ladle furnaces have an important role in the future of steelmaking where CO 2 emissions have to be mitigated to an acceptable level. One way to address this goal is to optimize and improve the current practices by adjusting the chemistry and reactions with material additions or gas injections. These procedures would greatly benefit from on-line slag composition analysis. Since the electric arcs radiate throughout the melting, optical emission spectroscopy is a potential method for such analysis. In this study, optical emissions from the electric arc are measured in a laboratory environment. Dozens of atomic emission lines were correlated with Cr 2O 3, Fe 2O 3, Al 2O 3, SiO 2, MnO, MgO, CaO, CaF 2, V 2O 5, and Ni content of the slag together with correlation between CaF 2 and molecular optical emission bands of CaF. Optimal spectral resolution for industrial applications was deducted to be between 0.022 and 0.179 nm. © 2021, The Author(s). --//-- Published under the CC BY license.
We acknowledge the support of Research Fund for Coal and Steel under grant agreement No. 709923, Academy of Finland for Genome of Steel grant No. 311934, Business Finland for Grant No. 4478/31/2019, Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES